Práticas de letramento - Garrido, Valéria Batista (2008)
This work is an account of an experiment, the objective of which is the educational practice itself, insofar as Alphabetization and Literacy is concerned. What was sought was to think of how to teach children in the phase of schooling, so that the education in reading and the education in writing have sense and meaning. The study occurred in a public state school of the city of São Paulo, in a 1st grade class of Fundamental Education. It is understood that the education to read and the education to write are put into effect within the perspective of Literacy, due to the fact that they are related as social practices. What is used as a source of data collection are open interviews with students, written material, produced by the students, as well as notations made from the observation of classes, such as diaries, students’ notebooks, surveys and the registration of classes. It is concluded that the manner in which the students learn is directly related to the manner of teaching of the professors. Consequently, a significant and contextualized teaching has greater possibilities of achieving success in the education of students, as was proven in this study, with the development of a project that provided an education in reading and writing as a social practice and the constant access to diversified written material. Effective learning by students was achieved